PROGRESS IN NON-TRADITIONAL POWER ENGINEERING - Strebkov, Dmitry (Energy and Automation, 2016)
The twentieth century was the last age of cheap energy. The era of cheap energy is over, and we need new energy technologies in order to ensure the sustainable future development. The review aims to find economic, reliable, renewable and non-polluting energy sources for future power engineering. Advanced tendencies in future power engineering are presented. The forecast for development of electric and power engineering in 21 century is discussed.